KEHIDUPAN SOSIAL EKONOMI ORANG-ORANG TIONGHOA DI KOTA JAMBI - Siti Heidi Karmela, Satriyo Pamungkas (Universitas Batanghari Jambi, 2017)
One of the ethnic that came to the Jambi is Tionghoa or mosstly knows as China. There are two kinds of them China Totok and China Peranakan. Most of them work as merchants, and they are dominated in economic localy, especially in Jambi, for example restaurants, banks, farms, automobile, and many more. All of these economic activities are influenced by confusionism theory. The content of it such as economical, honest, hard – working, and save. There are different between China Totok and China Peranakan, such as languages, reliance, relatives system, life style and their insight about Indonesia. China Totok still have strong feeling or conection identity with their ancestors, but China Peranakan who have acculturation and they feel that they are Indonesian. Keyword : Tionghoa, Tiongkok, Cina Totok, Cina Peranakan, Social Economic, Jambi City.